KELEMBAGAAN IMPLEMENTASI PROGRAM KREDIT MIKRO PERUMAHAN DI KOTA SEMARANG - Wido Prananing Tyas; Endah Ruswanti (TEKNIK, 2008)
Housing microfinance is the latest program launched by Kemenpera since 2006. The program is aimed tohelp the low-income household by giving subsidy for new home construction and renovation. During itsimplementation, microfinance institution as an implementer has some internal problems, such as humanresource, management, financial, trustment, accountability and limited links. Because of the problems, thisstudy is important to explore the institutional framework of the housing microfinance implementation inSemarang. The aim of the present study is to identify the institutional framework of the housingmicrofinance implementation in Semarang, not only by the government as a facilitator but also by themicrofinance institutions as an implementer and the inhabitants of this capital as a user. In this research,there are three focus discussions, including institution as an implementer of the housing microfinanceprogram, variables of the microfinance institutional framework, and the last, comparison study of thehousing microfinance implementation by the microfinance institutions in Semarang and comparisonbetween implementation in Semarang and the other developing countries. The study is utilizing qualitativeresearch method by describing the implementation of housing microfinance and exploring its institutionalframework to give some detail descriptions of the housing microfinance implementation in Semarang